PRINCIPLES OF ISLAMIC ECONOMIC TRANSACTION ACADEMIC IN REDUCING MORAL HAZARD (International Conference on Social and Islamic Studies, 2022)
The purpose of this paper is to analyze the principles of contract in Islamic economic transactions that can reduce the moral hazard that occurs in economic transaction activities. One of the things that triggers moral hazard is the existence of information asymmetry or information that is not balanced in these business activities, one of which is the rise of various kinds of fraud in online business activities that occur anywhere and anytime. This happens due to several factors, namely pressure, opportunity, rationality and capability. Furthermore, these factors will be reduced with preventive efforts, namely by internalizing contract principles in Islamic economic transactions. The research method used is a qualitative descriptive research design that aims to obtain a complete description of the principles of Islamic economic transaction contracts in reducing moral hazard using the religiosity and critical paradigm approaches. the divine principle, the principle of permissibility, the principle of justice, the principle of equality, the principle of honesty and so on can minimize the occurrence of moral hazard in economic activity.